History of the Triumphs of Our Holy Faith amongst the Most Barbarous and Fierce Peoples of the New World (University of Arizona Press, 2021)
Considered by historian Herbert E. Bolton to be one of the greatest books ever written in the West, Andrés Pérez de Ribas's history of the Jesuit missions provides unusual insight into Spanish and Indian relations during the colonial period in Northern New Spain. First published in Madrid in 1645, it traces the history of the missions from 1591 to 1643 and includes letters from Jesuit annual reports and other correspondence, much of which has never been found or cataloged in historical archives. Daniel T. Reff, Maureen Ahern, and Richard K. Danford have now prepared the first complete, scholarly, and fully annotated edition of this important work in English. Pérez de Ribas was the first permanent missionary to the Ahome, Zuaque, and Yaqui Indians. After fifteen years on the mission frontier he was recalled to Mexico City, where he held various posts, including Jesuit Provincial. Addressed to novitiates ignorant of the challenges they would face in the field, his Historia was a virtual textbook on missionary work in the New World. Also written to encourage ongoing support of the Jesuit missions, it reflected the author's deep grasp of what rhetorically soothed and moved Church and Crown officials. Perhaps of greatest interest to the modern reader are Pérez de Ribas's often detailed comments on indigenous beliefs and practices. These firsthand observations provide a rich resource of ethnographic and historical data concerning everything from native subsistence, settlement patterns, and myths to the dynamics of Jesuit-Indian relations. The many cases of conversion that Pérez de Ribas describes are especially rich in ethnographic data, clarifying the values and beliefs from which the Indians were "rescued." History of the Triumphs is a primary document of great importance, made more valuable here by an exceptionally fluid translation and painstaking annotations. It will be a standard reference for all engaged in research on New Spain and a captivating read for anyone interested in this chapter of American history.